2023
DOI: 10.3390/nu15051168
|View full text |Cite
|
Sign up to set email alerts
|

Food Hardness Modulates Behavior, Cognition, and Brain Activation: A Systematic Review of Animal and Human Studies

Abstract: Food hardness is one of the dietary features that may impact brain functions. We performed a systematic review to evaluate the effect of food hardness (hard food versus soft food diet) on behavior, cognition, and brain activation in animals and humans (PROSPERO ID: CRD42021254204). The search was conducted on 29 June 2022 using Medline (Ovid), Embase, and Web of Science databases. Data were extracted, tabulated by food hardness as an intervention, and summarized by qualitative synthesis. The SYRCLE and JBI too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
0
0
0
Order By: Relevance
“…In addition to these findings, the present study suggests that older adults with a lower occlusal force or smaller occlusal contact area tend to avoid foods that are considered difficult to chew and thus prefer soft and easily chewable foods. A systematic review of animal and human studies demonstrated the beneficial effects of dietary food hardness on behavior, cognition, and brain function [30]. If such eating habits persist for years, inactivity of the masticatory muscles can lead to a vicious cycle of further disuse atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these findings, the present study suggests that older adults with a lower occlusal force or smaller occlusal contact area tend to avoid foods that are considered difficult to chew and thus prefer soft and easily chewable foods. A systematic review of animal and human studies demonstrated the beneficial effects of dietary food hardness on behavior, cognition, and brain function [30]. If such eating habits persist for years, inactivity of the masticatory muscles can lead to a vicious cycle of further disuse atrophy.…”
Section: Discussionmentioning
confidence: 99%